2014
DOI: 10.1007/s00134-014-3502-6
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus bloodstream infections are associated with a higher energy deficit than other ICU-acquired bacteremia

Abstract: Early in-ICU energy deficit was associated with MRSA ICU-BSI in prolonged acute mechanically ventilated patients. Results suggest that limiting the early energy deficit could be a way to optimize MRSA ICU-BSI prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Cumulated energy deficit build-up during the first days of ICU stay appears an independent factor contributing to nosocomial infections. In their interesting study, Ekpe et al [47] investigated the impact of energy deficit on the microbiological results of the blood cultures of prolonged acute mechanically ventilated patients who experienced a first ICU-BSI episode. Daily energy balance was compared according to the microbiological results of the blood cultures of 92 consecutive prolonged ([96 h) acute mechanically ventilated patients who developed a first episode of ICU-BSI.…”
Section: Bacteremia and Mrsamentioning
confidence: 99%
“…Cumulated energy deficit build-up during the first days of ICU stay appears an independent factor contributing to nosocomial infections. In their interesting study, Ekpe et al [47] investigated the impact of energy deficit on the microbiological results of the blood cultures of prolonged acute mechanically ventilated patients who experienced a first ICU-BSI episode. Daily energy balance was compared according to the microbiological results of the blood cultures of 92 consecutive prolonged ([96 h) acute mechanically ventilated patients who developed a first episode of ICU-BSI.…”
Section: Bacteremia and Mrsamentioning
confidence: 99%
“…Another study has shown that progressive increase of enteral feeds delivery up to an energy target measured by indirect calorimetry, intermittently supplemented by PN, reduces the risk of nosocomial infections [12]. Epke et al [13] recently showed that an energy deficit during the first days in the ICU is associated with MRSA bloodstream infection in prolonged mechanically ventilated patients and suggested that limiting this energy deficit could optimize their prevention.…”
Section: Unrecognized Overfeeding Has Created Confusionmentioning
confidence: 99%
“…The recently published study by Ekpe et al [11] stresses once again the importance of achieving appropriate energy goals. The study, which investigated the impact of energy deficits on the microbiological results of blood cultures of long-term severely ill mechanical ventilation patients, confirms previous publications associating large energy deficits with infectious complications [12].…”
mentioning
confidence: 99%